A fatal case of rhinocerebral mucormycosis of the jaw after dental extractions and review of literature - Shilpa Prabhu; Manaf Alqahtani; Mohammed Al Shehabi (Elsevier, 2018)
The purpose of presenting this case is to report a fatal case of rhinocerebral mucormycosis post-dental extraction in a patient with uncontrolled diabetes mellitus. Several cases of rhinocerebral mucormycosis have been reported, but mucocutaneous mucormycosis has not been commonly reported to be a part of polymicrobial wound infections at multifocal sites. To the best of author's knowledge, this is the second case of polymicrobial rhinocerebral infection involving mucormycosis. Keywords: Mucormycosis, Rhinocerebral, Polymicrobial, Diabetes mellitus, Fungal infection, Immune dysfunction